The Checks of the Council: Local Horizontal Accountability’S Effects on Municipal Corruption in Latin America - Ordonez-Astete, M (Routledge, 2025)
Municipal councils in Latin America are usually expected to restrain the local executive, thus keeping them responsive to local demands, preventing the misuse of public resources, and ensuring the quality of local democracies. However, they regularly fail to perform this role adequately, thus allowing local executives’ abusive or arbitrary behavior. The literature on horizontal accountability and anti-corruption strategies highlights the relevance of accountability agents in preventing corruption, but they rarely assess the effectiveness of these activities. Based on the comparative method and relying on qualitative and administrative information, this article analyzes oversight activities that councils perform to control or prevent corruption in ten municipalities from Santiago de Chile. Amidst severe deficiencies in councilors’ formal accountability tools, the article contends that councilors, armed with resources, enhanced constituent support, and executive involvement, can rejuvenate and informally expand their formal tools. This empowerment facilitates local executive accountability and deters municipal corruption. © 2025 Taylor & Francis Group, LLC.